The Influence of Environmental Knowledge and Environmental Concern on Purchase Intention of Green Personal Care Products, Mediated by Green Trust Among Generation Z in Bali - Ida Ayu Swahastuti; Nilna Muna (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze the influence of environmental knowledge and environmental concern on the purchase intention of green personal care products, with green trust serving as a mediating variable among Generation Z in Bali. A quantitative approach was used, employing a survey of 210 respondents, and the data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that environmental knowledge and environmental concern have a positive and significant influence on green trust. Furthermore, green trust has a strong and significant effect on the purchase intention of green personal care products. The findings also confirm that green trust serves as a mediator, strengthening the relationship between environmental knowledge, environmental concern, and purchase intention. This study provides valuable insights into the behavior of young consumers who are increasingly aware of sustainability, as well as the importance of building trust through transparency and ethical commitment in marketing strategies for eco-friendly products.